Effects of cumulated outdoor activity on wildlife habitat use. (January 2021) - Corradini, Andrea; Randles, Matthias; Pedrotti, Luca; van Loon, Emiel; Passoni, Gioele; Oberosler, Valentina; Rovero, Francesco; Tattoni, Clara; Ciolli, Marco; Cagnacci, Francesca
Abstract: Humans profoundly affect animal distributions by directly competing for space, not only transforming, but actively using their habitat. Anthropogenic disturbance is usually measured via structural proxies such as infrastructure and land use that overlook the impact of human presence, or functional disturbance. In this study, we propose a methodology unifying two paradigms, human mobility and animal movement, to fill this gap. We developed a novel spatially-explicit index of anthropic disturbance, the Cumulative Outdoor activity Index (COI), and validated it with ground truth observations derived from camera trapping (r = +0.63, p  < 0.001). Building on previous work from Peters et al. (2015, Biol. Cons. 186, 123–133) on a Critically Endangered brown bear population in the Alps, we used Resource Selection Analysis to assess the influence of different forms of anthropogenic disturbance on the relative probability of habitat selection. The intensity of COI provided an effective measure of functional anthropogenic disturbance, and it outperformed all alternative and commonly-used proxies of structural disturbance in predicting bear habitat use. Our predictions suggest that brown bear shrinks its ecological niche as a consequence of intense human use of otherwise suitable habitat. These constraints may limit the potential range expansion of bears to establish a viable Alpine-Dinaric metapopulation. Conclusive conservation and future land use planning towards human-wildlife coexistence should account for the functional presence of humans on the landscape. The proposed COI could help determine where mitigation measures should be enforced. Highlights: Structural anthropic disturbance underestimates human-wildlife competition for space. We developed the Cumulative Outdoor activity Index (COI) based on human mobility data. COI best predicted brown bear space use in a reintroduced endangered population. Predictions indicate limits for the establishment of an Alpine bear metapopulation. COI can identify where to enforce human mobility restrictions for conservation purposes.